Efeitos dos agentes eletrofísicos no tratamento da dor, função respiratória pós-mastopexia com implantes e no processo de cicatrização de úlceras venosas - Pacheco, Esteban Ignacio Fortuny (Universidade Federal de São Carlos, 2024)
The use of electrophysical agents in postoperative treatment and tissue healing are key pillars of the work of physiotherapists dedicated to tissue repair. In countries outside Brazil, there is great concern to have a greater scientific basis for their use and to justify their application in chronic pathologies as well as in acute problems. The inclusion of some resources to optimize the healing of chronic wounds (venous ulcers) and to reduce postoperative pain are topics of great interest to patients, clinicians and their family support network. Our research group designed two studies to address these topics of great relevance for physical therapy and that represent a major impact on public health and patient recovery.
Effects of electrophysical agents in the treatment of pain, respiratory function after mastopexy with implants, and in the healing process of venous ulcers
Keywords: Humanos; Úlcera varicosa; Úlcera; Úlcera de perna; Lasers; Terapia de luz de baixo nível; Fotobiomodulação; Terapia de luz; Cicatrização de feridas; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL